2023
DOI: 10.3389/fimmu.2023.1091753
|View full text |Cite
|
Sign up to set email alerts
|

Resolvin D1/N-formyl peptide receptor 2 ameliorates paclitaxel-induced neuropathic pain through the activation of IL-10/Nrf2/HO-1 pathway in mice

Abstract: IntroductionPaclitaxel is a chemotherapy drug that is commonly used to treat cancer, but it can cause paclitaxel-induced neuropathic pain (PINP) as a side effect. Resolvin D1 (RvD1) has been shown to be effective in promoting the resolution of inflammation and chronic pain. In this study, we evaluated the effects of RvD1 on PINP and its underlying mechanisms in mice.MethodsBehavioral analysis was used to assess the establishment of the PINP mouse model and to test the effects of RvD1 or other formulations on m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 71 publications
(78 reference statements)
0
8
0
Order By: Relevance
“…Moreover, RvD1 reduced M1 macrophage activity and increased IL-10 expression and anti-inflammatory cytokines in the DRG and sciatic nerve [105]. Sexual dimorphism of RvD5 was reported in the mechanical allodynia regulation of TRPV1 or TRPA1 knock-out CIPN mice [105].…”
Section: Chemotherapy-induced Peripheral Neuropathy (Cipn) Pain Modelmentioning
confidence: 95%
See 3 more Smart Citations
“…Moreover, RvD1 reduced M1 macrophage activity and increased IL-10 expression and anti-inflammatory cytokines in the DRG and sciatic nerve [105]. Sexual dimorphism of RvD5 was reported in the mechanical allodynia regulation of TRPV1 or TRPA1 knock-out CIPN mice [105].…”
Section: Chemotherapy-induced Peripheral Neuropathy (Cipn) Pain Modelmentioning
confidence: 95%
“…Therefore, several studies have demonstrated the analgesic effects of Rv series using the CIPN mouse model. Intraperitoneal injection of RvD1 on day 1 after paclitaxel injection attenuated mechanical allodynia and thermal hyperalgesia in response to heat and cold stimuli [105]. Moreover, RvD1 reduced M1 macrophage activity and increased IL-10 expression and anti-inflammatory cytokines in the DRG and sciatic nerve [105].…”
Section: Chemotherapy-induced Peripheral Neuropathy (Cipn) Pain Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Nrf2 is also under the control of many other regulators, such as Akt ( Chen et al, 2022 ), Sirtuins ( Pan et al, 2016 ), IL-10 ( Su et al, 2023 ), and MAPK signaling ( Sun et al, 2009 ), all safeguarding cells from oxidative stress. Under normal conditions, Nrf2 is tightly regulated by the Keap1-CUL3-RBX1 E3 ubiquitin ligase complex, leading to Nrf2 degradation via the ubiquitin-proteasome pathway.…”
Section: Nrf2/ho-1 Axis Regulationmentioning
confidence: 99%